Influence of Leaf Physical Form and Heating on the Antioxidant Potential of Curry Leaves (Murraya koenigii) - W.M.A.P. Wanigasekera; MGCSB Gunarathna; SHNP De Silva (Journal of Food Innovation, Nutrition, and Environmental Sciences)
The study evaluated the effect of leaf physical form and heating on antioxidant activity, total phenolic content and flavonoid content of Murraya koenigii. Aqueous extracts were prepared from compound leaves and leaflets in two forms:  powder and whole leaves. Antioxidant activity (IC50) was assessed using the DPPH (2,2-Diphenyl-1-Picrylhydrazyl) assay, while total phenolic and flavonoid contents were measured by Folin-Ciocalteu and aluminium chloride colorimetric methods respectively. Antioxidant activity, phenolic content, and flavonoid content of Murraya koenigii extracts varied significantly with leaf form and heating duration. Powdered compound leaves and powdered leaflets exhibited the strongest antioxidant activity, with an IC50 of 0.0679 and 0.0764 mg/ml, respectively, while whole leaves demonstrated significantly weaker activity. Heating time significantly influenced antioxidant activity (P < 0.05). with an overall trend of improved activity at longer durations (15-60 minutes). However, the actual values at shorter durations (5-10 minutes) particularly in powdered forms, also showed strong activity, indicating that antioxidant levels did not consistently increase with prolonged heating. The highest phenolic content was recorded in powdered compound leaves at 45 minutes (43.66 ± 1.03 mg GAE/g), while the average across all treatments at this time point was 34.19 mg GAE/g. Prolonged heating significantly enhanced total phenolic content across all leaf forms (P < 0.05). The highest flavonoid content was in powdered leaflets at 5 minutes (36.21 ± 0.33 mg QE/g), with an average peak of 33.13 mg QE/g at the 45 minutes.  Flavonoid levels also increased significantly with heating across all leaf forms (P<0.05). A highly significant interaction (P < 0.001) between leaf form and heating duration was observed, indicating the combined impact on Murraya koenigii‘s antioxidant potential.